2006
DOI: 10.1007/s11373-005-9060-8
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of caldesmon during smooth muscle contraction and cell migration or proliferation

Abstract: SummaryThe actin-binding protein caldesmon (CaD) exists both in smooth muscle (the heavy isoform, h-CaD) and non-muscle cells (the light isoform, l-CaD). In smooth muscles h-CaD binds to myosin and actin simultaneously and modulates the actomyosin interaction. In non-muscle cells l-CaD binds to actin and stabilizes the actin stress fibers; it may also mediate the interaction between actin and non-muscle myosins. Both h-and l-CaD are phosphorylated in vivo upon stimulation. The major phosphorylation sites of h-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 68 publications
2
59
0
Order By: Relevance
“…Low-molecularmass isoforms of caldesmon (l-caldesmon, 70 to 80 kDa) are thought to be widely distributed in nonmuscle tissues, but only a few studies have used immunohistochemistry to investigate the distribution of caldesmon in selected tissues Fujita et al 1984;Ishimura et al 1984). l-Caldesmon has a role in the organization and stabilization of the microfilament network, thus regulating proliferation and migration (Kordowska et al 2006;Yokouchi et al 2006;Morita et al 2007). High-molecular-mass isoforms (h-caldesmon, 120 to 150 kDa) are predominantly expressed in differentiated smooth-muscle cells (SMCs), with only a few reported exceptions; platelets, colorectal pericryptal fibroblasts, and myoepithelial cells of galactophorous sinuses of human breast tissue contain h-caldesmon as well (Kakiuchi et al 1983;Frid et al 1992;Lazard et al 1993;Nakayama et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Low-molecularmass isoforms of caldesmon (l-caldesmon, 70 to 80 kDa) are thought to be widely distributed in nonmuscle tissues, but only a few studies have used immunohistochemistry to investigate the distribution of caldesmon in selected tissues Fujita et al 1984;Ishimura et al 1984). l-Caldesmon has a role in the organization and stabilization of the microfilament network, thus regulating proliferation and migration (Kordowska et al 2006;Yokouchi et al 2006;Morita et al 2007). High-molecular-mass isoforms (h-caldesmon, 120 to 150 kDa) are predominantly expressed in differentiated smooth-muscle cells (SMCs), with only a few reported exceptions; platelets, colorectal pericryptal fibroblasts, and myoepithelial cells of galactophorous sinuses of human breast tissue contain h-caldesmon as well (Kakiuchi et al 1983;Frid et al 1992;Lazard et al 1993;Nakayama et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…[96] In blood vessels, the endothelium plays an [97] , including endothelium-derived hyperpolarizing factor (EDHF), nitric oxide (NO), prostacyclins and epoxyeicosatrienoic acids. [98] In spite of this, it is demonstrated that the vaso-relaxation induced by FGAL is independent of EDRF, since it relaxes rat aorta both in the absence and presence of endothelium in an equipotent manner.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…The phosphorylation of caldesmon by MEK/ERK seems to regulate smooth muscle contraction. [96] In this process MEK/ERK is activated by PKC which in turn is stimulated by induced by fluoride causing relaxation, thereby inhibiting Rho-kinase or MEK activity. [124] www.wjpps.com contractions and PE induced contractions at similar dose ranges.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…In addition, it allows an interaction between the thin and thick filaments as it is able to bind to both actin and myosin and this property seems to be involved in the sustained phase of the contractile response (Marston et al, 1991). In vitro studies have shown that caldesmon can be a substrate for several kinases (Kordowska et al, 2006).…”
Section: Caldesmonmentioning
confidence: 99%